2004
DOI: 10.3310/hta8120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost-effectiveness of neonatal screening for inborn errors of metabolism using tandem mass spectrometry: a systematic review

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 86 publications
2
85
0
3
Order By: Relevance
“…When last considered in the UK in 2004, HT1 did not meet the criteria for NBS as the sensitivity and specificity of screening methods available at that time were unclear and in addition there were uncertainties about the efficacy of available treatments and how time critical their introduction was 18. The four cases reported here were detected as an unintended consequence of conventional NBS for PKU.…”
Section: Discussionmentioning
confidence: 93%
“…When last considered in the UK in 2004, HT1 did not meet the criteria for NBS as the sensitivity and specificity of screening methods available at that time were unclear and in addition there were uncertainties about the efficacy of available treatments and how time critical their introduction was 18. The four cases reported here were detected as an unintended consequence of conventional NBS for PKU.…”
Section: Discussionmentioning
confidence: 93%
“…A systematic review of published economic evaluations of NBS (reported in Chapter 6) identified five studies that included a cost associated with information provision related to NBS. [119][120][121][122][123] In the two identified studies relevant to the UK setting, 119,120 an incremental cost of providing information, based on the additional time that it would take a midwife to explain the additional tests being evaluated, was used (£0.30 119 and £0.40 120 ). Pandor et al 119 provided little information on how the cost they used was derived, but did refer to being informed by a consultation with a midwife.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK-based analysis, Pandor et al 119 included a unit cost of £0.30 (2001 prices) per baby screened to account for the extra (incremental) time taken by a midwife to explain the test, although the actual length of additional time was not specified. This cost was identified through a consultation with a midwife.…”
Section: Existing Evidence On the Costs Of Information Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] At present, MS/MS is being used for screening and diagnosis of IEMs in newborns and sick infants in many clinical biochemical laboratories in the USA, Europe, Australia, Japan, and other countries. [4][5][6][7][8][9][10][11] SQUH is the main referral hospital for IEMs in Oman. An organized diagnostic service for IEMs for high-risk babies was established at SQUH in 1998.…”
Section: Introductionmentioning
confidence: 99%